Crystal structure of (μ2-[2,2′-bis(diphenylphosphino)-1,1′-binaphthalene oxide-κ2O,P])-iodido copper(I), C44H32CuIOP2 - Wang Ying-Feng; Li Si-Fan; Lin Sen; Cui Yang-Zhe; Jin Qiong-Hua (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C44H32CuIOP2, monoclinic, P21/c (no. 14), a = 17.1995(14) Å, b = 11.4175(9) Å, c = 19.1704(17) Å, β = 104.263(2)°, V = 3648.5(5) Å3, Z = 4, Rgt(F) = 0.0464, wRref(F2) = 0.1387, T = 298(2) K.